ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KOPERASI (STUDI KASUS : KOPERASI DI SURABAYA UTARA) (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
The cooperative is one of the business drivers of growth in the economy that is owned and operated by people-a for the sake of the interests of members. The role of cooperatives is very important for all people in financial transactions. In the North of Surabaya itself, there are 92 cooperatives spread across 5 districts. This study uses qualitative and quantitative methods. This study uses primary and secondary data where the method of collection using the questionnaire. The population in this study is a cooperative-cooperative in the North of Surabaya which amounted to 92 of the cooperative. This study will describe about the causal relationship, so this method of using the sample and hypotheses. The technical analysis in this research is multiple linear regression analysis, coefficient of determination (r2) and hypothesis test using T test and f test. The results from this study were obtained from multiple linear regression analysis is Y = 6.818 + 0.143 X1 + 0.485 X2 + 0.438 X3 + e. The T test for independent variable participation (X1), commitment (X2) and the ability to innovate (X3) have a significant effect on the dependent variable performance (Y). The value of the F test has a probability value of significance of 0.000 < 0.05, where the variable participation (X1), commitment (X2) and the ability to innovate (X3) together significant effect on the significance on the performance (Y). Conclusion in this study is the independent variable participation (X1), commitment (X2) and the ability to innovate (X3) have a significant effect on the performance (Y).